Returning Citizens and Point of Entry: Is There a Match?. Issue 2 (April 2021) - Fogel, Sondra J.; Lersch, Kim M.; Ringhoff, Daniel; Grosholz, Jessica M.
The period after incarceration and the influence of neighborhood effects are gaining interest among scholars as a small body of evidence is illustrating the difficulties returning citizens have obtaining basic services and needs, employment, stable housing, and other social and behavioral health supports in the areas where they are being released. Transitional planning efforts to ensure that returning citizens are prepared to engage in society and have necessary supports are often made. However, returning citizens may be in local communities that do not offer needed supports, such as in areas of high poverty and criminal activity, and low employment options. Findings from this study suggest that more attention is needed to where returning citizens are released following their period of incarceration.